Structural Equation Modeling of Schema with Readiness of Addiction with the Mediator Variables Stress Coping Strategies and Cognitive Regulation of Emotion in Addicts with Drug Rehabilitation - Mahnaz Elahinezhad; Hossein Ebrahimi Moghadam; Rahim Davari (Shahid Sadoughi University of Medical Sciences, 2023)
Background: This study aims to model structural relationships of schema with the readiness of addiction with the mediation variables stress coping strategies and cognitive regulation of emotion in addicts with drug rehabilitation. Methods: This study is analytical-cross-sectional The sample consisted of 300 addicts with drug rehabilitation (18-55 years old) from 4 addiction treatment centers in 1401 in Amol city were selected based on stratified random sampling method. The questionnaire used in this study was Schema, Readiness of Addiction, stress coping strategies and cognitive regulation of emotion questionnaires. Analysis of data was performed based on the structural equations modeling in the software Amos 22. Sobel's test was used to examine mediating variables. Results: Findings showed that the schema affects the readiness for addiction with the mediation variables stress coping strategies and cognitive regulation of emotion in addicts with drug rehabilitation. The schema had a direct relationship with stress coping strategies in addicts with drug rehabilitation. It had a direct relationship with cognitive emotion regulation in addicts with drug rehabilitation. Cognitive emotion regulation had a direct relationship with susceptibility to addiction in drug addicts with drug rehabilitation. Stress coping strategies had a direct relationship with susceptibility for addiction in drug addicts with drug rehabilitation. Conclusion: Considering the predictive power of the variables, the results can be used in interventions and trainings in addiction treatment clinics.